Mechanisms and therapeutic perspectives of mitochondrial dysfunction of macrophages in periodontitis - Jia, Yibing; Li, Zili; Huang, Pengjie; Wang, Yan; Yang, Bo (Frontiers in Cellular and Infection Microbiology, 2025)
Periodontitis is a global inflammatory oral disease, and plaque-induced host excessive immune response is recognized as a major cause of its pathogenesis. In recent years, the relevance of mitochondrial dysfunction to periodontitis has been increasingly investigated, particularly with respect to macrophages, the key immune cells in the periodontal immune microenvironment. Mitochondrial dysfunction drives macrophage M1 polarization and osteoclast differentiation through mechanisms such as metabolic reprogramming, reactive oxygen species release, abnormal mitophagy, abnormal mitochondrial biogenesis and damaged mitochondrial dynamic. In addition, mitochondrial transfer in the periodontitis setting has been reported in several researches. In this review, we highlight the impact of mitochondrial dysfunction on macrophages in the periodontitis setting and summarize emerging therapeutic strategies for targeting mitochondria in periodontitis, including antioxidants, modulators of metabolic reprogramming, nanomaterials and photodynamic therapy.